Relevansi Pemikiran K.H. Abdul Halim Iskandar Terhadap Pedidikan Islam di Masa Kontemporer - Muhaimin, Mohammad; Nurlaela, Andi (Edukasi: Journal of Educational Research, 2021)
K.H. Abdul Halim is a prominent reformer in the field of education in Majalengka. Starting from childhood to adult K.H. Abdul Halim've got the education of the religious. Education obtained that provide a huge impact for change and education in Majalengka. K.H. Abdul Halim has the concept of thinking about education, namely As a Greeting. With the concept already has a contribution of big to education at that time. This research has purpose to know the thoughts K.H. Abdul Halim against the education of islam and how the relevance of the thought of K.H. Abdul Halim about the islamic education to education today.in this study using the method of Literature review. That refers to various suber that are relevant to the study of research. K.H. Abdul Halim has thought about the islamic education in which an education that not only berpatok on the relationship with God that is worship, but should have good relationships with humans. The point which a student it should be equipped with the knowledge, not just the science of religion, but also must be supported with the interests and talents of students, as well as how to live in a society.